Coexistence of chronic lymphocytic thyroiditis and papillary thyroid carcinoma. Impact on presentation, management, and outcome. (April 2016) - Dobrinja, C.; Makovac, P.; Pastoricchio, M.; Cipolat Mis, T.; Bernardi, S.; Fabris, B.; Piscopello, L.; de Manzini, N.
Abstract: Background: The association between chronic lymphocytic thyroiditis (CLT) and papillary thyroid carcinoma (PTC) has been investigated for several years from different perspectives. In spite of that, there were only few attempts to design a common frame of references to understand the complex mutual interactions between the various pathways of inflammatory response and of thyroid tumor induction and progression. This study compares two independent groups of patients aiming to determine the frequency and the prognostic significance of CLT in patients with PTC. Material and methods: From January 2005 to September 2013, we conducted a retrospective study on 160 patients with PTC who underwent thyroidectomy. CLT was diagnosed histopathologically. Age, sex, tumor features (dimensions, angioinvasion, capsular infiltration, mono/multifocality and lymph node metastases) pathologic findings and outcome were considered. Mean follow-up (metastasis, completeness-of-resection, serum thyroglobulin levels, tumor recurrence) period was 61 months (ranged from 18 to 132 months). A p < 0.05 was considered statistically significant. Results: Patients were divided in 2 groups. In group A there were 90 patients affected by PTC alone, and in group B there were 70 patients affected with PTC associated with CLT. Our data showed that the presence of CLT correlate with a lower grade of PTC (p < 0.05). Considering the sex of the patients there were a statistically significant correlation (p < 0.02) and the presence of CLT associated with PTC was most representative in female patients. Conclusions: The presence of CLT in patients with PTC correlated with a lower grade of PTC, but it does not affect the overall survival of papillary thyroid cancers.